Teacher's Interactional Feedback in “Teen Conversation 1” Class - Shellania Hariningsih (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study is done to find out (1) the types of interactional feedback used by the teacher of Teen Conversation 1 Class and (2) the types of interactional feedback used by the teacher of Teen Conversation 1 Class toward each of the student. In order to answer the research questions, the writer chose the types of interactional feedback by Nassaji (2015) as her guideline. This study is a qualitative research. The writer collected the data by audio recording the classroom activities of Teen Conversation 1 Class and having a semi-structured interview with the teacher. The findings of this study show that five out of seven types of interactional feedback appeared in the classroom. The five types of interactional feedback found in the class were Recast, Direct Correction, Clarification Request, Direct Elicitation, and Metalinguistic cues. Recast, especially Declarative Recast was the type of feedback used the most by the teacher. In conclusion, the teacher used different types of interactional feedback to each of the student, concerning their different needs and weaknesses.